Research and industry Discussion on issues of technology transfer, intellectual property and spin-off - Francini, Franco; Sansoni, Paola (Il Colle di Galileo, 2014)
The event was an opportunity to study topics of Technology Transfer, Intellectual Property and Spin-off in order to encourage the process of exchange and collaboration between research institutions, local authorities and specialized companies.